Implementación de un biodigestor a base de residuos orgánicos en la Universidad Técnica de Cotopaxi campus Salache. - Cruz Herrera, Anderson David (2023)
The research work was carried out with the objective of determining the level of effectiveness and efficiency of the implementation of a biodigester based on organic waste at the Technical University of Cotopaxi, Salache Campus. A quantitative methodology was used focused on the creation of a database about the amount of organic waste obtained in "the stable and potato place", the amount of organic waste in 7 days was 174.55kg, this amount was used to feed the biodigester, obtaining a per capita generation of 0.22 kg/inhab/day, which is less than the estimated value of generation in Ecuador (0.58 kg/inhab/day). A batch biodigester fed by the organic wastes obtained was built, allowing the generation of biogas after 35 days and obtaining a significantly higher amount at 42 days, which was its highest point. To check the effectiveness and efficiency of the biodigester, the energy efficiency of the waste entering the biodigester was calculated. The result showed that it is not feasible to use a biodigester based on organic waste at the Technical University of Cotopaxi..